The Role of Language Representation of the Time Model in the Process of Meaning Creation - Voronina, Larisa V.; Skokova, Tatyana N.; Melnikova, Yulia N.; Yarygina, Olga N.; Miroshnichenko, Galina G. (Journal of History Culture and Art Research, 2018)
The aim of the article is to demonstrate the language picture of the world, which owes its structural integrity to its relational framework. The archetype “time” is central to the Christian mythology, in fairy tales and other linguocultural artefacts. The thought-language essences representing the category TIME in the modern German language, connect different time modes (past, present, future), allowing to distinguish different worlds. The memory of the ways of the development of the human soul is concentrated in them. The analysis is carried out on the material of propositional structures of substantive derivatives, representing the category TIME in modern German. In particular, the article illustrates the process of modelling knowledge of the category TIME when coupled with the ability to establish relationships between an individual unit of measure as a part and its component as an integral (PART – WHOLE), and between integrity and individuality (INTEGRAL – PART). The nouns generated on the basis of the WHOLE – PART structure are profiled by the ʽdurationʼ attribute, correlated with a certain length of time. Cognitively selected in the structure of the PART – WHOLE is a certain period of time. The propositional structure TIME –SITUATION characterizes time as a duration limited by the framework of existence of a certain state. Moreover, time correlated with certain events can profile the sign of ʽextensibilityʼ, objectified by terms of length. In the composition of the cognitive structure of the derived substance, a concept representing a TIME or a SITUATION and a concept modelling spatial relations can interact. The corresponding fragment / event on the linear time axis is cognitively highlighted in the conceptual structure of such a name. Thus, the use of the modelling technique creates a demonstrative basis for the fact that the language representation of the refraction of the world picture through the prism of the time model allows us to learn not only the processes of meaningfulness, but also to reveal the secret of the meaning of existence being unique to each person.